Reliability based live loads for structural assessment of bridges on heavy-haul railway lines - Kabani, Matongo (Department of Civil Engineering, 2019)
The highest live loads on railway lines are on dedicated freight corridors operated as heavy-haul lines. These lines carry high axle loads above 25 tonnes and total tonnage above 20 million tonnes per annum over distances greater than 150km. The South African iron ore line currently operates long trains of length 4.1km with 30 tonne per axle wagons on a narrow gage (1065mm) line over a distance of 861km. The operation of heavy haul lines require close monitoring and structural performance evaluation of existing bridges. This study covered both analytical studies and field measurements of bridge dynamic response and static vertical loads required to compute moments shear for beam-type bridges. The field study of dynamic amplification factors was based on strain measurements on the Olifants bridge located on the heavy-haul iron line in South Africa. The Olifants bridge is a 23 span box girder consisting of 2 continuous span segments of 11 spans at either end and a drop span in the middle. The collected strain data consisted 1174 loaded and 1372 empty train crossing events from June 2016 to March 2017. The probabilistic study was based on weigh-in-motion data of heavy-haul freight collected from January 2016 to August 2016. The study was limited to single span, 2 span and 4 span bridges with equal spans and did not consider fatigue. The dynamic response parameters of interest were frequency time evolution of bridge under heavy loads and dynamic amplification factors. An approximate formula derived using 2 dimensional beam model with moving masses is presented. The approximate formulae predicts the reduced frequency within 12% of the estimate from field vibration measurements of an 11 span continuous bridge with train to bridge linear mass ratio of 88%. The approximate formula underestimates the frequency as the stiffening contribution from train suspension system is ignored in a moving mass approximation. Dynamic amplification factors from strain measurements of a continuous 11 span bridge where considerably higher with maximum of 12% compared to 5% from a moving force analytical model for train speed below 60km/h. The amplification from measurements were considerably higher due to the additional local amplification of strains in upper flange of the box girder. A comparison of amplification factors for loaded and empty trains shows that increase in gross weight increases amplification factors. Furthermore, dynamic amplification factors are not dependent on changes in speed during train crossing. Different extrapolation techniques were used to obtain load effects from the same block maxima data. It was shown that the normal, GEV and Bayesian extrapolation methods give load effects within 1% of each other with the normal extrapolation being marginally on the lower end. This observation holds across beam types and span lengths from 5m to 50m. Although the GEV allows for all the three extreme type distributions, an analysis based on available weigh-in-motion data of axle weights show that the fitted distributions using Bayesian and Maximum Likelihood Estimate for all load effects for the span ranges are all Weibull type. On the other hand it is known that the domain of attraction for the normal distribution is Gumbel type. The study also found that extrapolated loads effects are less sensitive to increase in return period beyond 50 years. This aspect is significant as return period is a measure of safety target when determining design values for loads. The study investigated the impact of traffic volume increase and wagon axle load dependencies. The load effects on heavy-haul were shown to be more sensitive to the weak dependence than to traffic growth over the remaining service life of 50 years. The increase in return levels of load effects is less than 1% for traffic volume growth of 4% over a period of 50 years in contrast to the much higher values between 6% and 9% reported on highway bridges for 3% traffic volume growth over 40 year period. Assessment loads that account for some wagon axle dependence have lower return values of load effects than the assume that axle loads are independent which is consistent with theory.